Impelementasi Payment Gateway untuk System Management Member Gym Menggunakan Framework Laravel 10 - Wibowo, Beautifully Margaretha Putri; Asmiatun, Siti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Public interest in sports is increasing from time to time. People are starting to realize the importance of maintaining body health and encouraging themselves to exercise more regularly and maintain a healthier lifestyle. Various types of sports can be done ranging from light exercise to competitive sports. One of the sports that has become a trend lately is exercising indoors with modern sports equipment facilities, such as gyms. Even though gyms have provided various needed facilities, people still have some obstacles experienced, such as lack of free time to be able to book sports facilities and pay for facilities directly. Therefore, the researcher developed a gym member management system by utilizing Laravel 10 as the back-end system and Midtrans as an online payment provider, as well as applying the Agile Software Development method which includes the stages of planning, design, development, testing, deployment, and review as a benchmark in system design. Thus, the gym member management system can help users book sports facilities anywhere and anytime through membership and simplify payment transactions by implementing online payments, as well as provide a new experience for users in booking gym facilities and improve operational efficiency.